Optimization of PV/T Solar Collector Performance with Fuzzy If-Then Rules Generation - Khalili, N.N.W. (Springer Science and Business Media B.V., 2021)
Solar energy has been a great resource of energy that help to fulfill the worldâs energy demand. However, the surrounding conditions affect the performance of a photovoltaic/thermal solar collector greatly. Since the operation of air photovoltaic/thermal solar collector involves energy input to generate the air flow, it is important to ensure balance in the input and output energy. Based on the experimental data collected, membership functions have been developed and a set of rules has been generated using graphical method to ensure the optimization of the solar collector performance under changes of environmental factor such as solar radiation and ambient temperature. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.